2016
DOI: 10.1016/j.jcmgh.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

New and Unexpected Biological Functions for the Src-Homology 2 Domain-Containing Phosphatase SHP-2 in the Gastrointestinal Tract

Abstract: SHP-2 is a tyrosine phosphatase expressed in most embryonic and adult tissues. SHP-2 regulates many cellular functions including growth, differentiation, migration, and survival. Genetic and biochemical evidence show that SHP-2 is required for rat sarcoma viral oncogene/extracellular signal-regulated kinases mitogen-activated protein kinase pathway activation by most tyrosine kinase receptors, as well as by G-protein–coupled and cytokine receptors. In addition, SHP-2 can regulate the Janus kinase/signal transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 123 publications
1
18
0
2
Order By: Relevance
“…Rats with renal I/R injury have higher IL-6, TNF-α, IL-1β and SHP27 expression in serum with reperfusion time prolonging. Notes: TNF-α, tumor necrosis factor-α; IL-6, interleukin-6; SHP-2, Src homology 2 domain-containing protein tyrosine phosphatase 2; LPS, lipopolysaccharide; NC, negative control; *, p < 0.05 vs. the sham group; #, p < 0.05 vs. the model-blank group As a tyrosine phosphatase, SHP-2 is highly correlated with multiple cell signaling processes, such as growth, survival, proliferation, differentiation and apoptosis, and is particularly important in chronic inflammation [23]. The current study demonstrated that the silencing of SHP-2 inhibited the release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Rats with renal I/R injury have higher IL-6, TNF-α, IL-1β and SHP27 expression in serum with reperfusion time prolonging. Notes: TNF-α, tumor necrosis factor-α; IL-6, interleukin-6; SHP-2, Src homology 2 domain-containing protein tyrosine phosphatase 2; LPS, lipopolysaccharide; NC, negative control; *, p < 0.05 vs. the sham group; #, p < 0.05 vs. the model-blank group As a tyrosine phosphatase, SHP-2 is highly correlated with multiple cell signaling processes, such as growth, survival, proliferation, differentiation and apoptosis, and is particularly important in chronic inflammation [23]. The current study demonstrated that the silencing of SHP-2 inhibited the release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, SHP099 did not suppress the downstream signalling pathways examined in CHS‐3, a HS line that produces SHP2 p.Glu76Gln. SHP2 also is known to be involved in a variety of signalling pathways such as the NF‐κB, JNK, Wnt/β‐catenin, Hippo and RhoA pathways, suggesting that SHP2 activates growth in CHS‐3 by utilizing signalling pathway(s) other than ERK, AKT and STAT3. Alternatively, because SHP2 variants may have different affinities for SHP099 depending on the relative time spent in the open and closed states by proteins with different types of mutations, concentrations that allow for SHP099 to inhibit phosphorylation of ERK and/or AKT could exceed the SHP099 concentration (1 μM) used in CHS‐3.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[44][45][46] It is noteworthy that CagA targets and triggers the Src-homology phosphatase-2 (SHP-2), which directly interacts with YAP1 and potentiates its cotranscriptional function. 47,48 This tripartite connection of CagA/SHP2/YAP1 may be critical in the early phases of human gastric carcinogenesis. 49 Nuclear localization of YAP1 is thus the sum of multiple, possibly parallel, regulatory layers.…”
Section: Lats2 and Yap1 Interdependence In H Pylori-infected Gastricmentioning
confidence: 98%